Validity Analysis of Socio-Scientific Issues (SSI)-Based Student Worksheets on Climate Change Using Aiken’s V - Rabiatul Hasanah (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2026)
This study aimed to analyze the validity of a Socio-Scientific Issues (SSI)-based student worksheet on climate change using Aiken’s V index. The study was conducted as part of research and development employing the 4D model, with a specific focus on the develop stage, particularly expert validation and product revision. Three validators assessed 20 items covering five aspects: content feasibility, SSI characteristics, construction and presentation, language, and graphic design. Data were collected using a validation form with a five-point rating scale and quantitatively analyzed using Aiken’s V index. The validators’ comments and suggestions were analyzed descriptively and used as the basis for product revision. The results showed that the Aiken’s V values for individual items ranged from 0.667 to 0.917. Nine items were categorized as highly valid, while eleven items were categorized as valid. The overall mean validity score was 0.779, indicating that the worksheet was valid. The construction and presentation aspect obtained the highest validity score of 0.813, whereas the language aspect received the lowest score of 0.750. The components requiring further improvement were primarily related to the depth of the learning content, the adequacy of scientific data and evidence, consistency in the use of scientific terminology, and coherence of the learning activity sequence. Therefore, the SSI-based student worksheet on climate change was considered valid and suitable for classroom trials after minor revisions were made in accordance with the validators’ recommendations.